Visible-Light-Induced Aerobic Oxidation of Benzylic C(sp3)–H of Alkylarenes Promoted by DDQ, tert-Butyl Nitrite, and Acetic Acid - Pan, Decheng; Wang, Yiqing; Li, Meichao; Hu, Xinquan; Sun, Nan; Jin, Liqun; Hu, Baoxiang; Shen, Zhenlu (Synlett, 2019)
A visible-light photocatalytic aerobic oxidation of benzylic C(sp3)–H bonds proceeded in the presence of 2,3-dichloro-5,6-dicyano-1,4-benzoquinone, tert-butyl nitrite, and acetic acid. Advantages of this aerobic oxidation method include its relatively mild conditions, the use of visible-light irradiation instead of conventional thermal methods, the use of a low catalyst loading, and the ability to oxidize a range of alkylarenes, including xanthenes, thioxanthenes, and 9,10-dihydroacridines, to the corresponding ketones in excellent yields.
Keywords: xanthenones; thioxanthenones; acridinones; oxidation; photocatalysis; benzylic oxidation